2009
DOI: 10.1212/wnl.0b013e3181c1de77
|View full text |Cite
|
Sign up to set email alerts
|

Cortical event-related potentials in preclinical familial Alzheimer disease

Abstract: Auditory sensory and cognitive cortical potentials in persons with familial Alzheimer disease (FAD) mutations are abnormal approximately 10 years before dementia will be manifest. Longer event-related potential latencies suggest slowing of cortical information processing in FAD mutation carriers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
70
2
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(85 citation statements)
references
References 36 publications
9
70
2
4
Order By: Relevance
“…It also greatly improved our understanding of the neurophysiological underpinnings of various clinical disorders. Nowadays, for example, auditory ERPs are being used to study the neurodevelopmental status of persons with language development problems [4], Alzheimer's disease [5], and autism [6].…”
Section: Introductionmentioning
confidence: 99%
“…It also greatly improved our understanding of the neurophysiological underpinnings of various clinical disorders. Nowadays, for example, auditory ERPs are being used to study the neurodevelopmental status of persons with language development problems [4], Alzheimer's disease [5], and autism [6].…”
Section: Introductionmentioning
confidence: 99%
“…7 Studies have proposed ERPs as a sensitive method for early detection of AD, separating EEG activity related to AD pathology from normal aging. [8][9][10][11][12] Preclinical markers and early detection are increasingly …”
mentioning
confidence: 99%
“…7 Studies have proposed ERPs as a sensitive method for early detection of AD, separating EEG activity related to AD pathology from normal aging. [8][9][10][11][12] Preclinical markers and early detection are increasingly important as research on new treatments that may slow or halt decline in AD are under development. 13,14 Familial AD (FAD) allows the study of presymptomatic stages of AD that may be relevant for sporadic AD.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…By inference, delayed P300 latencies (by 2SD) or reduced P300 amplitudes were considered features of dementia, and thus useful diagnostic tools [40]. Based on this method, several studies found delays or amplitude decreases of P300 recorded from posterior (Pz) derivations in patients with putative AD [41], subcortical dementia [42], metabolic disorders [43] e PDD [44]. Yet, dementia categorization in the last ten years has been revolutionized by the identification of DLB, representing from 25 to 43% of all dementia cases.…”
Section: P 300 Abnormalitiesmentioning
confidence: 99%